2006
DOI: 10.1002/bmc.602
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of 8-oxo-7,8-dihydro-2′-deoxyguanosine in urine by high-performance liquid chromatography after pre-column derivatization with glyoxal reagents

Abstract: A new, simple and sensitive pre-column fluorescence derivatization high-performance liquid chromatographic method for the determination of the oxidative DNA stress marker, 8-oxo-7,8-dihydro-2'-deoxyguanosine, was developed. Solid-phase extraction using an Oasis HLB cartridge avoided troublesome sample preparation steps, interference from charged species and frequent and essential electrode maintenance in electrochemical procedures. 8-Oxo-7,8-dihydro-2'-deoxyguanosine and other guanine compounds were selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results revealed that an excess of MTNG is required (MTNG:8-nitroG molar ratio 3740:1, Figure 2 ) to completely derivatize 8-nitroG in DNA hydrolysates. This may be attributable to the fact that MTNG reacts not only with 8-nitroG but also with other guanine compounds present in biological samples [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that an excess of MTNG is required (MTNG:8-nitroG molar ratio 3740:1, Figure 2 ) to completely derivatize 8-nitroG in DNA hydrolysates. This may be attributable to the fact that MTNG reacts not only with 8-nitroG but also with other guanine compounds present in biological samples [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-microliter DNA samples were spiked with 50 μL of 5 nM [ 13 C 2 , 15 N]-8-nitroG and subjected to acid hydrolysis in 100 μL of 1 N HCl for 30 min at 80 °C, followed by neutralization with 100 μL of 1 N NaOH. 8-NitroG derivatization and reaction buffer used were described previously [ 24 , 27 , 35 ] and was performed with some modifications. Reaction buffer was prepared by combining 10 mL of 20 mM sodium acetate buffer (pH 4.8), 1 mL of 3 M sodium acetate buffer (pH 5.1) and 1 mL of 1 M Tris-HCl buffer (pH 8.0), aliquoted and stored at −20 °C.…”
Section: Methodsmentioning
confidence: 99%